P817 Live-vaccines and lactation in newborn exposed in utero to anti-TNF: A multi-centre French experience in inflammatory bowel disease. (16th January 2018) - Bendaoud, S; Nahon, S; Gornet, J -M; Pariente, B; Beaugerie, L; Abitbol, V; Peyrin-Biroulet, L; Buisson, A; Hebuterne, X; Altwegg, R; Amil, M; Rosa, I; et al.
Abstract: Background: Anti TNF cross placenta during pregnancy and are detectable in the newborn in the first 6 months at least. European consensus recommends to avoid live vaccines within 6 months of live in newborn exposed in utero to anti TNF. These treatments are of low risk for breastfed infants but data are scarce. The aim of our study was to evaluate the rate and tolerance 1) of live-vaccines before and after 6 months of life in newborn exposed in utero to anti TNF and 2) of breast-feeding under anti TNF Methods: We performed an observational and retrospective study in 28 French departments of gastroenterology from February 2016 to September 2017. Included patients were inflammatory bowel disease (IBD) women, pregnant under anti TNF, giving birth to alive newborn and agree to answer a questionnaire concerning (1) live-vaccines (BCG, rotavirus, MMR)in their child during first year, (2) breast-feeding and complication and (3) information given during pregnancy Results: A total of 143 pregnant women treated with anti-TNF were included; 113 (79%) for Crohn's disease and 30 (21%) for ulcerative colitis. The mean age was 31.5 year (IQR 5). Anti-TNF was Infliximab in 8 (60%) patients, Adalimumab in 53 (37%) patients, Certolizumab in 3 patient (2%) and Golimumab in 1 patient. Thiopurine was associated in 30 (21%) patients. 35 (24.5%) patients experienced flare of IBD during pregnancy. Anti-TNF was discontinued before 26 gestational weeks in 74 (52%) women and resumed after delivery in 131 (92%) patients. 63 women (45%) breastfed their infant and no complication was noted. Among 76 women who did not perform lactation, 49 (64.5%) did not for personal choice and 27 (35.5%) because not recommended by the gastroenterologist. Concerning vaccination questionnaires, 120 responses were obtained. BCG was performed in 33 children (27.5%) and was administered before 6 months in 19 children (16%). One local abscess was reported with favourable evolution. Rotavirus vaccination was performed in 7 children (6%) and before 6 months in 5 cases. One case of fever was reported. MMR vaccination was performed in 72 children (60%), before 6 months in 6 cases. Information concerning foetal exposure to anti-TNF and vaccination recommendation was given to 127 (89%) IBD women during pregnancy, by at least the gastroenterologist in 123 (86%) of cases, the obstetrician in 23%of cases and the paediatrician in 12% of cases. Conclusions: Half of women breastfed their child with no reported complication. BCG was administered in 30% of the newborn and performed before 6 months in 50% of cases, with only one case of local abscess. Rotavirus vaccination is rare but often performed before 6 months. Information to pregnant IBD women is only given by gastroenterologist in the majority of cases. Information by obstetrician and paediatrician should be improved.